Perancangan Buku Saku Elektronik Penggunaan Kode Diagnosis JKN Rumah Sakit Soeharto Heerdjan - Purba, Andrea Krisler; Muchlis, Husni Abdul; Hosizah, Hosizah; Ambarwati, Ambarwati; Muzdalifah, Ifah (Akademi Perekam dan Informasi Kesehatan Imelda, 2026)
Hospitals frequently encounter challenges in the BPJS Kesehatan claims process, such as diagnostic coding errors, data discrepancies, and incomplete medical record documentation. These issues result in claims delays, financial disruptions, and a decline in service quality. This study aims to design an electronic pocketbook of National Health Insurance (JKN) diagnosis codes as a guide for healthcare workers to expedite and simplify the claims process. The study was conducted at Soeharto Heerdjan Hospital from October to December 2024 using the Research and Development (R&D) method with the ADDIE model in three stages: analysis, design, and development. Six informants from the analysis and coding unit and the patient verification and assurance unit were involved as data sources. Data collection techniques included in-depth interviews, questionnaires, and document reviews, followed by descriptive analysis. The results showed that the 34-page electronic pocketbook, designed in PDF format, contains diagnoses, ICD-10 codes, severity levels, and management procedures, with hyperlinks for easy information retrieval. The feasibility test showed a validity level of 95.8% for content and 91.6% for media. Therefore, this pocketbook is highly valid and suitable for use as a guide in the BPJS claims process, and can support work efficiency and improve the quality of hospital services.